Answer:
![\textsf{33.} \quad y=-x^2-2x+3](https://img.qammunity.org/2023/formulas/mathematics/college/zubjkiw5p79dnocnvn1a5ku32btgdwkczl.png)
![\textsf{34.} \quad y = x^2+4x+3](https://img.qammunity.org/2023/formulas/mathematics/college/bosdgzgov7n6mqtzm751bku5rdclc3l2u3.png)
Explanation:
Question 33
Factored form of a quadratic equation:
![\boxed{y=a(x-r_1)(x-r_2)}](https://img.qammunity.org/2023/formulas/mathematics/college/j20yam5b9tz80ixme4w1480svasphj89pr.png)
where:
- a is the leading coefficient.
- r₁ and r₂ are the roots.
From inspection of the graph:
- r₁ = -3
- r₂ = 1
- vertex = (-1, 4)
Substitute the roots and the vertex into the formula and solve for
:
![\begin{aligned}y & =a(x-r_1)(x-r_2)\\\implies 4 & = a(-1-(-3))(-1-1)\\4 & = a(2)(-2)\\4 & = -4a\\-4a & = 4\\(-4a)/(-4) & = (4)/(-4)\\a & = -1\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/7qpsip2x5dkl6a3d2by8h98qm7931632e4.png)
Substitute the found value of
and the roots into the formula and rewrite in standard form:
![\begin{aligned}y & =a(x-r_1)(x-r_2)\\\implies y & = -1(x-(-3))(x-1)\\y & = -(x+3)(x-1)\\y & = -(x^2+2x-3)\\y & = -x^2-2x+3\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/oke20muhnfz8bp4dg98ec9t935w13xnxkr.png)
Therefore, the equation of the parabola in standard form is:
![y=-x^2-2x+3](https://img.qammunity.org/2023/formulas/mathematics/college/54tirimynrs6s35cx0f7gjmlpoq3k5ar6w.png)
Question 34
Vertex form of a quadratic equation:
![\boxed{y=a(x-h)^2+k}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lvp7xwe62mxkmylhlneh35g6onw1d1noj2.png)
where:
- (h, k) is the vertex.
- a is some constant.
From inspection of the graph:
- Vertex = (-2, -1) ⇒ h = -2 and k = -1
- y-intercept = (0, 3)
Substitute the vertex and y-intercept into the formula and solve for
:
![\begin{aligned}y & = a(x-h)^2+k\\\implies 3 & = a(0-(-2))^2+(-1)\\3 & = a(0+2)^2-1\\3 & = 4a-1\\3 +1& = 4a-1+1\\4 & = 4a\\4a & = 4\\(4a)/(4) & = (4)/(4)\\a & = 1\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/95rvqkbw3lwxjki6xpsjfuavsp78t806r0.png)
Substitute the found value of
and the vertex into the formula and rewrite in standard form:
![\begin{aligned}y & = a(x-h)^2+k\\\implies y & = 1(x-(-2))^2+(-1)\\y & = (x+2)^2-1\\y & = (x+2)(x+2)-1\\y & = x^2+4x+4-1\\y & = x^2+4x+3\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/xdysj5l15fpantf6btn778hcqxuq8hy9uw.png)
Therefore, the equation of the parabola in standard form is:
![y & = x^2+4x+3](https://img.qammunity.org/2023/formulas/mathematics/college/8t7nr1brkcybrnw1556g87dduu0r5ok11l.png)